Re-touche: Re-Stitching Fissures Through Affect in Families with a Family Member who is Labelled as Disabled - Vandecasteele, Marieke; De Schauwer, Elisabeth; Blockmans, Inge; Van Hove, Geert (Art/Research International)

(untitled) (University of Alberta, 2021)
Creativity and affect in families with a family member, who is labelled as disabled, is central in this article. These families are often pinned down to individual, closed categories where everything revolves around the label “disability.” Our research goes beyond binary thinking in terms of abled/disabled and other linear explanations by using artistic processes as ethnography. We start from encounters between two people who both created something about their “non-ordinary” brothers. One (first author) made a shortfilm/documentary about her own family, the other (research participant) wrote a TV series about a man who takes care of his brother after their mother’s death, which was not autobiographical yet inspired by his own experiences. The first author distilled etchings from their encounters, which piece together different layers: the scenarist’s biographical story, the story of creating the series, the series’ script and the first author’s thoughts and readings. The concept of re-touche—of touching and being touched, and in this way returning to family fissures and creating something new from them—runs through this art-based project.